MAbDelivery: Administration routes for antibody therapy Third LabEx MAbImprove industrial workshop, July 2, 2015 Tours, France. Issue 4 (19th May 2017) - Bodier-Montagutelli, Elsa; Respaud, Renaud; Watier, Hervé; Guillon-Munos, Audrey
ABSTRACT: The annual "LabEx MAbImprove Industrial Workshops" are primarily intended to provide a comprehensive view about topics of interest for the pharmaceutical industry to scientists involved in research on therapeutic antibodies. The third workshop in this series, held July 2, 2015 in Tours, was dedicated to the optimization of delivery, namely all processes leading monoclonal antibodies to reach their target site. The commonly used intravenous (IV) route, although advantageous in terms of pharmacokinetics and pharmacodynamics, presents some disadvantages in terms of patients' convenience, therapeutic target access or treatment cost. Such problems led pharmaceutical companies to consider more straightforward and patient-friendly administration routes, bringing the need for specific formulations adapted to the specific inherent physicochemical challenges. In this context, the workshop provided an overview of these advances and opened discussion on new administration routes and formulation development. In the first session, the opportunities and challenges of 3 main routes of administration (IV, subcutaneous (SC), and pulmonary) were discussed, integrating protein stability issues. The next session was dedicated to medical devices intended for SC and pulmonary administration. The last session focused on specific formulations for monoclonal antibodies, particularly to successfully protect antibodies upon aerosolization, to develop highly concentrated formulations for SC administration, and to use formulation as a mean to overcome the barriers to oral protein delivery. As in the previous editions, this workshop gathered people from the academic and industrial spheres and allowed rich debates and discussions.